Industry use of 'better-for-you' features on labels of sugar-containing beverages. Issue 18 (10th October 2018) - Brownbill, Aimee L; Miller, Caroline L; Braunack-Mayer, Annette J
Abstract: Objective: To examine the ways in which sugar-containing beverages are being portrayed as 'better-for-you' (BFY) via features on product labels. Design: Cross-sectional audit of beverage labels. Setting: Adelaide, Australia. Data on beverage labels were collected from seventeen grocery stores during September to November 2016. Subjects: The content of 945 sugar-containing beverages labels were analysed for explicit and implicit features positioning them as healthy or BFY. Results: The mean sugar content of beverages was high at 8·3 g/100 ml and most sugar-containing beverages (87·7 %) displayed features that position them as BFY. This was most commonly achieved by indicating the beverages are natural (76·8 %), or contain reduced or natural energy/sugar content (48·4 %), or through suggesting that they contribute to meeting bodily needs for nutrition (28·9 %) or health (15·1 %). Features positioning beverages as BFY were more common among certain categories of beverages, namely coconut waters, iced teas, sports drinks and juices. Conclusions: A large proportion of sugar-containing beverages use features on labels that position them as healthy or BFY despite containing high amounts of sugar.